The Relationship of Self-Efficacy with Academic Stress of Grade 9 Students at Madrasah Tsanawiyah: Hubungan Efikasi Diri dengan Stres Akademik Siswa Kelas 9 di Madrasah Tsanawiyah - Khasana, Wahyu Nur; Nastiti, Dwi (Psikologia : Jurnal Psikologi, 2022)
This research was conducted because it was motivated by the demands of Islamic-based schools (MTs) for their students. Where students must learn general subjects and subjects regarding religion, so students must understand them at once. This makes the teaching and learning process in schools spend more time than schools in general. This triggers the emergence of academic stress in students. This research was conducted with the aim to determine the relationship between self-efficacy and academic stress of students at MTs Negeri 1 Pasuruan. This type of research is quantitative research using a correlational approach. The variables in this study were the self-efficacy variable as the independent variable while the academic stress variable was the dependent variable. The measuring instrument used is a Likert scale measuring instrument with the population involved in this study, namely students of class IX at MTs Negeri 1 Pasuruan as many as 366 students. Based on the table of Issac and Michael, the total population of 366 with an error rate of 5% is between 380, so the sample used in this study was 182 students. The technique used is simple random sampling technique. Analysis of research data using product moment correlation using the help of the SPSS 16.0 for windows program. The results of the analysis show a value (-0.465) with a significance value of 0.000. So, there is a negative relationship between self-efficacy and academic stress. This means that the hypothesis given by the researcher can be accepted by the acquisition of the value of the effective contribution of self-efficacy with academic stress of 21.6%. Reliability on the self-efficacy scale showed a result of 0.908 while on the academic stress scale showed a result of 0.892.